Social phobia among Al Qadissya medical student: prevalence, Academic performance and response to different treatments - alkhafji, Abdul Zahra M. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Social phobia (SP) is an inappropriate anxiety; experienced in social situations in which the person feels observed by others and could be criticized by them so he/she attempts to avoid such situations. Objectives: This study aims to identify the prevalence of (SP) among the medical students, as well as the socio- demographic characters will be investigated.The effect of (SP) on the students that is; their academic performance and the response to different type of treatments. Methods: Three hundred eighty students of both genders were selected randomly from Al-Qadissia Medical College in Al- Diwania city. These students were interviewed using the International Diagnostic Checklist of ICD.10 Social Phobia. The academic performance of subjects meeting a diagnosis of (SP) was studied. Their response to selective serotonin reuptake inhibitor (Fluoxetine) and comprehensive cognitive behavioral therapy were evaluated. Results: The result showed that the prevalence of (SP) among the medical student is (12.6 %). female students had higher rates than males (17.4%, 7.9%) respectively. positive family history of any psychiatric disorder was found more in students having (SP) . Eating or speaking in public appeared to be the most common feared situations avoided by the diagnosed students. (SP) appeared to have no effect on the students academic performance. Both treatment (Fluoxetine, Comprehensive Cognitive Behavioral Therapy) had good response (48%, 52.8%) respectively. Conclusions: Significant differences are found between the rate of SP and different sexes. SP appeared to have no effect on the students academic performance. Both active treatments had good response; in addition they have nearly equal result.